Peningkatkan Ekonomi Petani Kopi Melalui Program Pengelolaan Hutan Bersama Masyarakat (PHBM) - Fitrianto, Jeri; Amin, Dang Eif Saiful (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2023)
The purpose of this study was to find out the LMDH business, also to know the process and results of LMDH in improving the economy of coffee farmer groups. The method used is a qualitative method with descriptive research. The results of this study indicate that the efforts made by LMDH in improving the economy of coffee farmers are by running a Perhutani program called the PHBM (Community Forest Management) program. The process carried out includes coffee farmers in Mekarmanik Village, Kec. Cimenyan Kab. Bandung has achieved all three stages, namely enabling, empowering and protecting the results of LMDH's efforts. Tangible results have occurred in the forest area in Mekarmanik Village since the start of the forest management program with the community. One of them is increasing the number of coffee plantation commodities in the forest area.